The impact of lower-limb function on upper-limb pull and push strength in elite handcycling athletes - Muchaxo, R. E. A.; Kouwijzer, I.; van der Woude, L. H. V.; Janssen, T. W. J.; Nooijen, C. F. J.; de Groot, S. (Sports Biomechanics, 2023)
This study investigated the impact of performing a closed kinetic chain with the lower limbs on isometric upper-limb pull and push strength. Sixty-two elite handcyclists were assessed with the Manual Muscle Test and allocated to groups with partial to normal (LLF) or no lower-limb (no-LLF) function. Both groups performed upper-limb strength measurements under two kinetic-chain conditions. During the closed-chain condition, the lower limbs were attached to two footrests, providing horizontal and vertical support. During the open-chain condition, the footrests were removed and the limbs were supported vertically by a horizontal plate. Repeated-measures ANOVA were conducted to investigate main effects (open vs. closed chain, LLF vs. no-LLF) and their interaction. During pull, LLF performed better (p < 0.001, +11%) by pushing against the footrests. However, this increase in pulling strength during a closed-chain condition was not observed in the no-LLF. Therefore, findings suggest an advantage for the least impaired athletes by being able to perform lower-limb closed chains during pulling. Handcyclists with LLF can maximise pulling performance by adjusting the footrests. The classification system should consider the implications of these findings on the allocation of athletes with different levels of LLF and/or on the equipment regulation.